GOVERNANCE, RISK, AND COMPLIANCE (GRC) IN STARTUP COMPANY: A CASE STUDY OF TANIHUB IN INDONESIA - Rizki Dito Subekti; Rifqi Irsyaad Fathi; Yahya Wuddy Yapono; Riza Nisfu (Universitas Trilogi, 2026)
This study examines the strategic role of Governance, Risk, and Compliance (GRC) in ensuring the sustainability of startups in Indonesia through a case study of PT TaniHub Indonesia. Despite its substantial funding, and a strong mission to empower farmers through digital platforms, TaniHub experienced severe operational and financial failure. This research argues that the company's collapse was driven primarily by structural weaknesses. The study adopts a qualitative approach using a Systematic Literature Review (SLR) combined with NVivo-assisted thematic analysis, drawing on 41 data sources including peer-reviewed journal articles, official reports, books, and news publications. The analysis is guided by the OCEG GRC Capability Model, which conceptualizes GRC through four dimensions: Learn, Align, Perform, and Review. The findings reveal systemic deficiencies across all four dimensions: TaniHub failed to institutionalize risk learning in strategic decision-making, showed misalignment between aggressive growth strategies and governance readiness, pursued innovation without adequate risk controls, and lacked structured review mechanisms for continuous improvement. The study reinforces that GRC should be understood as a strategic enabler rather than a procedural constraint, particularly in high-risk, trust-dependent sectors such as agritech and fintech. Keywords: Governance, Risk, and Compliance; Startup; Sustainability; TaniHub